In silico characterization and comparison of the fruit ripening related beta‐ amylase (BAM) gene family in banana genome A and B - Erdianty Setiabudi; Karlia Meitha; Fenny Martha Dwivany (Universitas Gadjah Mada, 2021)
Banana is one of the most important commodities for maintaining global food security. Primary metabolic processes during the ripening of banana greatly affect post‐harvest quality, particularly in starch metabolism. The beta‐ amylase (BAM) gene family is known as a group of genes that plays an important role in starch metabolism regulation. In this study, we focused on the characterization and comparative analysis of the BAM gene family in DH Pahang and Pisang Klutuk Wulung (PKW) varieties, these being the AA and BB genomes, respectively. The sequences of BAM gene family were retrieved from the database of Musa acuminata ’DH Pahang’ and Musa balbisiana ’PKW’ genome, then structural and functional characterization was performed, followed by identification of cis‐acting elements in the BAM promoter regions. The results showed that the BAM gene family structure was relatively conserved in both genomes, and a putative BAM11 gene was found, the function of which has not been studied in other plants. Cis‐acting element analysis showed that they were distinct in the copy number and types of elements that were responsive to various phytohormones. This study suggested that the BAM genes involved in ripening are spatiotemporally regulated. However, further functional genomic analysis is required to describe the specific role and regulation of BAM genes during ripening in banana.